Predictive biomarkers for response to EGFR-directed monoclonal antibodies for advanced squamous cell lung cancer. (14th June 2018) - Bonomi, P D; Gandara, D; Hirsch, F R; Kerr, K M; Obasaju, C; Paz-Ares, L; Bellomo, C; Bradley, J D; Bunn Jr, P A; Culligan, M; Jett, J R; Kim, E S; et al.
Abstract: Background: Upregulated expression and aberrant activation of the epidermal growth-factor receptor (EGFR) are found in lung cancer, making EGFR a relevant target for non-small-cell lung cancer (NSCLC). Treatment with anti-EGFR monoclonal antibodies (mAbs) is associated with modest improvement in overall survival in patients with squamous cell lung cancer (SqCLC) who have a significant unmet need for effective treatment options. While there is evidence that using EGFR gene copy number, EGFR mutation, and EGFR protein expression as biomarkers can help select patients who respond to treatment, it is important to consider biomarkers for response in patients treated with combination therapies that include EGFR mAbs. Design: Randomized trials of EGFR-directed mAbs cetuximab and necitumumab in combination with chemotherapy, immunotherapy, or antiangiogenic therapy in patients with advanced NSCLC, including SqCLC, were searched in the literature. Results of associations of potential biomarkers and outcomes were summarized. Results: Data from phase III clinical trials indicate that patients with NSCLC, including SqCLC, whose tumors express high levels of EGFR protein ( H -score of ≥200) and/or gene copy numbers of EGFR (e.g. ≥40% cells with ≥4 EGFR copies as detected by fluorescence in situ hybridization; gene amplification in ≥10% of analyzed cells) derive greater therapeutic benefits from EGFR-directed mAbs. Biomarker data are limited for EGFR mAbs used in combination with immunotherapy and are absent when used in combination with antiangiogenic agents. Conclusions: Therapy with EGFR-directed mAbs in combination with chemotherapy is associated with greater clinical benefits in patients with NSCLC, including SqCLC, whose tumors express high levels of EGFR protein and/or have increased EGFR gene copy number. These data support validating the role of these as biomarkers to identify those patients who derive the greatest clinical benefit from EGFR mAb therapy. However, data on biomarkers for EGFR-directed mAbs combined with immunotherapy or antiangiogenic agents remain limited.